The labor market returns to unobserved skills: Evidence from a gender quota - Safoura Moeeni; Feng Wei (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2022)
We estimate the effects of unobserved skills on labor market outcomes by investigating a change in the distribution of unobserved skills. Among people with the same levels of observed skills such as education and work experience, there are still disparities in labor market outcomes. since employers cannot observe all applicantsâ skills and productivity, they rely on the average skills of different groups. We exploit a discontinuity generated by the 2012 education policy in Iran. This policy restricting female students in specific college majors changes the size and skill distribution of high school graduates. We find three main findings. First, the education quota lowers women's college attendance. Second, young high-school graduate women are more likely to participate in the labor market and have a job. Third, the gender wage gap decreases among high-school workers due to both within and between occupation changes: treated women are paid more and they take up higher-paying middle-skilled positions that used to be non-traditional occupations for them.
Keywords: 330; Unobserved Skills; Occupational Choice; Education Quota; Gender Discrimination; Wage differentials